Writing Errors of English as Second Language (ESL) Learners in the 21st Philippine Context - Dania Munder (RIRAI Publisher, 2024)
To learn a second language (L2), once mastered, entails various prospects for Filipinos. One of the goals of the K-12 curriculum is to strengthen communicative competencies, which include linguistic competence; however, it was reported that the English Proficiency Index (EPI) of the Philippines has continuously declined in 2019, a year after the first batch of Senior High School graduated. As the country’s EPI declines, it may negatively impact the competitiveness of Filipinos in the international arena. Additionally, this result demonstrates the presence of errors in the writing performance of the learners despite the change in the curriculum. This research utilized a descriptive method to analyze the corpus from 100 ESL learners of a private school in Marawi City, Lanao del Sur. The findings illustrate that the majority, or 96.3221% were local errors and among these were mechanical or orthographic errors which ranked first with 1677 or 33.70%. Furthermore, the most committed error was misuse or omission of verb tenses, followed by capitalization and punctuation marks. With these results, it is important to expose learners to the target language (TL) and teachers to create remedial writing programs focusing on the weakest linguistic areas.